Randomization and social policy evaluation revisited - James J. Heckman (Centre for Microdata Methods and Practice (cemmap), 2020)
This paper examines the case for randomized controlled trials in economics. I revisit my previous paper "Randomization and Social Policy Evaluation" and update its message. I present a brief summary of the history of randomization in economics. I identify two waves of enthusiasm for the method as "Two Awakenings" because of the near-religious zeal associated with each wave. The First Wave substantially contributed to the development of microeconometrics because of the flawed nature of the experimental evidence. The Second Wave has improved experimental designs to avoid some of the technical statistical issues identified by econometricians in the wake of the First Wave. However, the deep conceptual issues about parameters estimated, and the economic interpretation and the policy relevance of the experimental results have not been addressed in the Second Wave.
Keywords: C93; 330; Field Experiments; Randomized Control Trials